Effect of short-term storage on semen quality and total antioxidant capacity in white cachama semen (Piaractus orinoquensis) (Revista Sistemas de Producción Agroecológicos, 2025)
The quality of white-faced cachama (Piaractus orinoquensis) semen is crucial for artificial reproduction. The temporary deterioration of semen in vitro limits its handling. The objective of this study was to evaluate the effect of short-term storage at room temperature on key quality parameters and the total antioxidant capacity (TAC) of semen from this species. Semen was collected from six hormonally induced males. Samples were kept at room temperature (~23°C) and evaluated at 0, 15, 30, and 60 minutes post-collection. Bulk motility (%), motility duration (s), pH, and TAC of seminal plasma were analyzed. Bulk motility remained high (>93%) during the first 30 minutes, but decreased significantly (p < 0.05) at 60 minutes (87.50 ± 6.12%). No significant differences (p > 0.05) were found in motility duration or total antioxidant capacity (0.389 ± 0.17 mM Trolox) over the 1-hour evaluation period. Seminal pH remained constant at 8.5. P. orinoquensis semen remained viable for at least 30 minutes at room temperature. The initial decline in sperm quality appears to be due to energy depletion rather than to depletion of the antioxidant system, which remained constant. A management window is established to optimize artificial fertilization protocols in this species.
Keywords: Piaractus orinoquensis; semen quality; short-term storage; oxidative stress; sperm motility